2019
DOI: 10.22159/ajpcr.2019.v12i3.29949
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Activity Herbaceous Vine - Tinospora Cordifolia

Abstract: Tinospora cordifolia (Willd.) Miers ex Hook. F. and Thoms is a large deciduous, climbing shrub found throughout India, especially in the tropical parts ascending to an altitude of 300 m and also in certain parts of China (Anonymous). It belongs to the family Menispermaceae. It is known as heart-leaved Moonseed plant in English, Guduchi in Sanskrit, and Giloy in Hindi. It is known for its immense application in the treatment of various diseases in the traditional ayurvedic literature. T. cordifolia, also named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Flavonoids, tannins, and lignins are the major components of polyphenols. The pharmacological effects of these polyphenols are mainly due to the antioxidant property in scavenging free radicals [22]. The present study results correspond with the earlier results indicating that Tinospora cordifolia Atenolol and Propranolol are selective β receptor antagonists that are used for the treatment of cardiovascular disease like, high blood pressure, coronary heart diseases, arrhythmias, angina pectoris and also reduce the risk of heart complications following MI [24,25].…”
Section: Discussionsupporting
confidence: 91%
“…Flavonoids, tannins, and lignins are the major components of polyphenols. The pharmacological effects of these polyphenols are mainly due to the antioxidant property in scavenging free radicals [22]. The present study results correspond with the earlier results indicating that Tinospora cordifolia Atenolol and Propranolol are selective β receptor antagonists that are used for the treatment of cardiovascular disease like, high blood pressure, coronary heart diseases, arrhythmias, angina pectoris and also reduce the risk of heart complications following MI [24,25].…”
Section: Discussionsupporting
confidence: 91%
“…Another study indicated that the ethanol extract of T. cordifolia stem which contains substantial amounts of phenols also has marked antioxidant activity [47]. The antioxidative activity of T. cordifolia is credited to its alkaloids and diterpenoid lactones such (-)epicatechin, tinosporin, isocolumbin and palmatine [48,49]. Consistently, T. crispa also possesses antioxidative activity.…”
Section: Discussionmentioning
confidence: 99%
“…If the plant growing on the neem tree is trained well, it will have a higher number of medicinal properties [ 18 ]. The plant is widespread across the tropics and subtropics, while it thrives best in dry, hot areas with plenty of moisture [ 19 ]. Discovery, reproduction, and survival of these fragile genotypes may rely heavily on biotechnological instruments.…”
Section: Methodsmentioning
confidence: 99%